The Influence of Service Quality and Facilities on the Performance of Medical and Non-Medical Staff at Bunda General Hospital Jakarta - Lestari Reza Widyastuti; Zaharuddin; Dudun Junaedi (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2025)
Customer-oriented service delivery highlights the significance of meeting user demands and ensuring expectations are addressed promptly and efficiently. Simultaneously, sufficient infrastructure and physical support systems are essential for building organizational values and enabling operational activities to achieve objectives. Job productivity refers to the output produced by individuals or teams within an institutional context. This research explores how service quality and infrastructural support impact the work effectiveness of healthcare and administrative personnel at Bunda General Hospital Jakarta. Data were obtained using a random sampling method from a total population of 415 employees, with a final sample of 81 respondents determined through Slovin’s formula (Husein Umar, 2017). Findings reveal that service quality and infrastructure, whether analyzed individually or collectively, significantly and positively affect staff performance in both medical and non-medical functions. Based on these findings, hospital management is advised to enhance service delivery standards, optimize infrastructure, ensure adequate human resource distribution, maintain facilities according to work programs, and, for future studies, expand variables for facility measurement.